2004
DOI: 10.1111/j.1468-2230.2004.00482.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulating Marriage and Cohabitation in 21st Century Britain

Abstract: This article assesses the legal regulation of marriage and cohabitation in Britain and outlines a growing need and desire for the currently confused law to be amended despite what has been termed 'the normal chaos of family law'. It adds to the topical debate about 'couple regulation' and argues that law should protect the function rather than the form of relationships. This argument is supported by recent Nu⁄eld Foundation funded research, which draws on a major attitudinal survey of over 3000 respondents' vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 0 publications
0
29
0
1
Order By: Relevance
“…The Argument for Realism Barlow andDuncan (2000a, 2000b) introduced this argument in a strong critique of New Labour policies concerned to promote the stability of families through marriage; their research, and approach, has now led to a substantial body of literature (Barlow et al 2005; 15 I am making the presumption that the reference to the Law Commission was not a 'burial' tactic. Given the subsequent timetable adopted by the Law Commission, I think we can deduce that this is a serious programme for consideration of reform.…”
Section: The Case For Reform: Realismmentioning
confidence: 99%
See 1 more Smart Citation
“…The Argument for Realism Barlow andDuncan (2000a, 2000b) introduced this argument in a strong critique of New Labour policies concerned to promote the stability of families through marriage; their research, and approach, has now led to a substantial body of literature (Barlow et al 2005; 15 I am making the presumption that the reference to the Law Commission was not a 'burial' tactic. Given the subsequent timetable adopted by the Law Commission, I think we can deduce that this is a serious programme for consideration of reform.…”
Section: The Case For Reform: Realismmentioning
confidence: 99%
“…Published version available in Feminist Legal Studies 14(2) 181-211 -9 - Barlow & James 2004;and see Barlow in this volume). Further, and adding a major impetus to their argument, they found in interviews with cohabitants that 56% of those questioned believed that they would receive some protection from family law in the event of property disputes.…”
Section: Kent Academic Repository -Kent Law Schoolmentioning
confidence: 99%
“…survey indicated that most people supported the same rights and obligations found in marriage being extended to cohabiting couples of longstanding, it is likely given their starting point that marriage is deserving of special treatment, that cohabitants will be offered something inferior to marriage but better than the confusion which is the current law (see further Barlow & James 2004). Whilst we could and arguably should classify all caregiving relationships in one legal category as suggested by Fineman (1995, p.231):…”
Section: Options For Reform -Ideals V Realitymentioning
confidence: 99%
“…Some commentators have argued that cohabitation is functionally identical to marriage (at least where children are involved): 81 namely a joint enterprise principally of sexual intimacy, companionship, emotional and fi nancial support, home making and child bearing and rearing, which is helpful to society as a whole… Arguments of this kind are neither uncontroversial nor clear, 82 and may conceal variations within cohabitation relationships and marriages. In addition, these arguments often seem to focus, as in the quotation above, on the existence of children, which might lead one to suggest that the distinction should not be between spouses and cohabitants but between parents and others.…”
Section: Cohabitation Marriage and Partnershipmentioning
confidence: 99%